PERANAN GREETER DALAM PENGOPERASIAN STANDAR OPERASIONAL PROSEDUR 18TH RESTORAN DI HOTEL THE TRANS LUXURY BANDUNG - Marshanda Ayu Nehaz; Dendi Gusnandi (Media Bina Ilmiah, 2024)
The role of the greeter in the operation of Standard Operating Procedures (SOP) at The Trans Luxury Hotel Bandung's restaurant is a crucial aspect of the service industry. The restaurant is located on the 18th floor of the hotel, renowned for its high-quality service and featuring 280 rooms. The hotel boasts 17 classroom-style meeting rooms, a ballroom, and the largest convention center in Bandung. The hotel operates under a luxury hotel concept with a high-class market segmentation.This study aims to investigate the role of the greeter in the operation of SOP at The Trans Luxury Hotel Bandung's restaurant. The research method employed is a descriptive study involving direct observation and interviews with one greeter and 15 customers. The results show that the greeter plays a crucial role in operating SOP at the restaurant. The greeter must be able to welcome guests warmly, guide them to their desired tables, help them sit, escort them, and see them out to the exit. However, some greeters do not adhere to the standard procedures. Therefore, the authors recommend that the restaurant management conduct stricter oversight of greeting procedures and motivate greeters to improve their service performance. This study is expected to serve as a consideration for hotel management, particularly in the restaurant, to enhance service quality and ensure that SOP is implemented properly. By doing so, it can enhance the guests' impression and improve the hotel's reputationreputation